2015
DOI: 10.1371/journal.pone.0119015
|View full text |Cite
|
Sign up to set email alerts
|

mLST8 Promotes mTOR-Mediated Tumor Progression

Abstract: The activity of the mechanistic target of rapamycin (mTOR) is elevated in various types of human cancers, implicating a role in tumor progression. However, the molecular mechanisms underlying mTOR upregulation remain unclear. In this study, we found that the expression of mLST8, a required subunit of both mTOR complex 1 (mTORC1) and complex 2 (mTORC2), was upregulated in several human colon and prostate cancer cell lines and tissues. Knockdown of mLST8 significantly suppressed mTORC1 and mTORC2 complex formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 39 publications
(40 reference statements)
9
41
0
Order By: Relevance
“…Previously, it has been reported in prostate carcinomas and advanced ovarian cancer that SOS1 overexpression correlates with cancer progression and with a shorter survival, indicating that its dysregulation is an essential requirement for tumorigenesis [17]. We noticed that MLTS8/GBL mRNA and protein were overexpressed in CC, its expression has been evaluated in other tumors, such as prostate and colon cancer, and contributes to tumor growth and invasion; in addition, strong protein expression has been observed in invasive cancer lesions [18].…”
Section: Discussionmentioning
confidence: 80%
“…Previously, it has been reported in prostate carcinomas and advanced ovarian cancer that SOS1 overexpression correlates with cancer progression and with a shorter survival, indicating that its dysregulation is an essential requirement for tumorigenesis [17]. We noticed that MLTS8/GBL mRNA and protein were overexpressed in CC, its expression has been evaluated in other tumors, such as prostate and colon cancer, and contributes to tumor growth and invasion; in addition, strong protein expression has been observed in invasive cancer lesions [18].…”
Section: Discussionmentioning
confidence: 80%
“…This contradiction may indicate a compensatory increase in mTOR transcription in response to inhibition of this pathway. However, the GEP data also showed that expression of Myotubularin-related protein 3 ( MTMR3 ), a negative mTOR complex 1 (mTORC1) regulator 43 , was increased, while that of mTOR-associated protein LST8 homolog ( MLST8 ), a required subunit and positive regulator of mTORC1 and mTORC2 44 , was decreased, supporting the possibility of mTOR inhibition. Moreover, these data are consistent with prior studies showing that BET inhibitors lowered phospho-inositide 3-kinase (PI3K) signaling, and dissociated BRD4 from chromatin at regulatory regions of the Insulin-like growth factor-1 receptor 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Although enhanced mTOR signaling activation has been reported to not be associated with the survival of some tumor patients, targeting mTOR signaling is still a reasonable approach for tumor radiotherapy [33][34][35][36]. Any protein in the PI3K/AKT/mTOR pathway can be targeted for the clinical inhibition of mTOR activation in tumor tissues [37,38]. In particular, clinically targeting mTOR signaling during radiotherapy could increase tumor radiosensitivity [39].…”
Section: Introductionmentioning
confidence: 99%